THE INFLUENCE OF GREEN RECRUITMENT PRACTICE ON ENVIRONMENTAL SUSTAINABILITY IN SELECTED SERVICE BASED STATE CORPORATIONS IN KENYA - Jeruto, Rael; Kwasira, Dr. Josphat; Chelule, Dr. Joel; Rop, Dr. Willitter (European Journal of Business and Strategic Management, 2017)
Purpose: The general objective of this study was to evaluate the influence of green recruitment practice on environmental sustainability in selected service based state corporations in Kenya Methodology: The study adopted a descriptive design but specifically a survey which involved collecting data from five state corporations in order to test hypotheses of the study. The target population was 13,940 management employees of the 170 state corporations. The sample size was 122 respondents; 22 top level management, 33 middle level management and 67 Supervisors/ line managers from five service based State Corporations in Nairobi. Multistage sampling was adopted to select the individual subjects randomly. Primary data was collected using a self - administered semi structured questionnaire.Descriptive statistics was used mainly to summarize the data. SPSS was used for analysing complex data. Regression analysis was used to establish the relationship between the independent and dependent variables. Data presentation was through the use of pie charts, bar charts, graphs and frequency tables. Results: The extent to which green recruitment practice was used in state corporation established that recruitment of staff who are green conscious, green employer branding and the establishment of a full department that handles green issues was extensively used. It was established that there was no green job descriptions for employees and that the organization did not encourage applicants to use green criteria when applying for jobs. Unique Contribution to Theory Practice and policy: This study aims at making policy recommendations based on the findings which can be used by State Corporations to establish a recruitment portal and ensure that employees who are environment conscious are recruited into the organization. The State Corporations should also ensure that the brand image of the corporation portray the green values of the organization